Outcomes of Silicone Oil Removal After Pars Plana Vitrectomy at A Tertiary Eye Hospital, Nepal - Manandhar, Ashma; Pradhan, Eli; Sharma, Sanjita; Duwal, Sushma; Thapa, Raba (Nepalese Journal of Ophthalmology, 2026)
Introduction: Silicone oil is used in complicated retinal detachment since many decades. It is associated with many complications so, silicone oil removal is to be done once the retina is attached. Retinal re-detachment is the most serious complication after its removal. Objective: To evaluate the surgical outcomes and ocular complications after silicone oil removal in cases of rhegmatogenous retinal detachment. Methodology: It was a hospital-based observational study conducted after ethical clearance among the patients that underwent silicone oil removal between 2018 January to 2018 December at Tilganga Institute of Ophthalmology. Consecutive sampling technique was used for the study. Inclusion criteria were patients undergoing silicone oil removal for the first time with or without cataract surgery during the study duration. Exclusion criteria were cases with retinal detachment noted at the time of silicone oil removal, patient younger than 18 years, scleral thinning at the site of sclerotomy, use of silicone oil tamponade other than 1000 centistoke. Visual acuity, intraocular pressure, retinal re-detachment, corneal complications were evaluated in this study. Result: Total 88 eyes of 88 patients (67.1% male) were included in this study. Mean age of the patient was 62 years with standard deviation of 3.4 years (range 37-75 years). Anatomically success was obtained in 75 (85.2%) cases. Best corrected visual acuity was improved in 43 (48.86%). Complications after oil removal were re-detachment of retina in 13 (14.8%), ocular hypotony two (2.27 %), ocular hypertension three (3.40%), corneal decompensation eight (9.09%). Conclusion: This study showed an overall improvement in post-operative visual acuity after silicone oil removal but anatomical success may not match the functional success in all cases. Retinal re-detachment remained the most common complication after the silicone oil removal.